Russia-Ukraine War and the Imperatives of a New Global Order - Abdulyakeen, Abdulrasheed; Mumuni, Nurain Abayomi (Journal of Contemporary International Relations and Diplomacy, 2024)
The Russia-Ukraine conflict has illuminated the inherent problems within the current global order and accentuated the urgent need for a re-imagined framework that addresses these issues. This study underscored the multifaceted nature of Russia-Ukraine War and the imperative of international efforts to seek a sustainable resolution. Using secondary data and content analysis. Findings reveal that Russia-Ukraine War is rooted in a complex web of historical, cultural, and geopolitical factors which the escalation of the conflict was exacerbated by issues related to the continuous encroachment of North Atlantic Treaty Organization (NATO) into territories considered to be sphere of influence of Russia, Crimea's annexation, the rights of Russian-speaking populations, and Ukraine's alignment with Western institutions. The study conclude that the conflict has contributed to a reevaluation of alliances and strategic partnerships on the global stage. It has also raised questions about the effectiveness of international institutions and the challenges posed by information warfare, energy security, and arms control. The study recommends that the international community should reaffirm its commitment to the principles enshrined in the United Nations Charter and other relevant agreements. Violations of these norms, as witnessed in Crimea, should be met with condemnation and diplomatic pressure.